Firm innovation in East Asia-Pacific region - ABUMOUSA, Ashraf D.M (KDI School, 2018)
This study shines a light on factors that affect innovation activities across seven countries in East Asia and Pacific region for the year of 2015. The study investigates the impact of governance environment, firm characteristics, and external finance on innovation of 4993 firms from Malaysia, Indonesia, Philippine, Vietnam, Timor Leste, Solomon Islands, and Papua New Guinea. The World Bank enterprise survey has been employed as the data source, I take cross sectional data includes public and private firms, large and SMEs in these countries. This paper defines three aspects of firm innovation, core innovation that refers to introducing or developing new product and/or services, innovation activities which include R&D spending, licensing inventions, international quality certificate, licensing new technology from foreign companies, and conducting in innovation training. The third aspect is related to the effectiveness of innovation new outputs whether they have new functions, better quality, new automation, or new process technology. I find that individual firm characteristics are strongly correlated to firm innovation. I also provide new evidence to the positive relationship between corruption and innovation as well as the preference of external finance to the internal finance in the context of firm innovation.
Thesis(Master) --KDI School:Master of Development Policy,2018